Development of a Liquid Hydrogen-Based Fuel Cell System for the HYDRA-2 Drone - Boer, P.C. de; Wit, A.J. de; Benthem, R.C. van (Netherlands Aerospace Centre NLR, 2021)
The aviation sector is actively pursuing a reduction to its environmental footprint. Liquid hydrogen-based propulsion is one of the key innovative technologies that is currently being explored. Before this technology can be introduced into the aviation sector, several obstacles have to be overcome such as infrastructure, propulsion system, and architecture of aircraft. To gain experience with the technology, NLR is currently deploying a ground-based infrastructure and developing a flight platform to assist research in this area. This paper discusses the development of the liquid hydrogen-based fuel cell system for the HYDRA-2 flight platform. In particular, this work discusses the design philosophy, material choices, relevant certification requirements for the LH2 storage tank and conditioning system. The remaining challenges and improvements of the design are outlined as well.
This report is based on a presentation held at the AIAA SciTech 2022 Forum, San Diego, CA & Virtual, January 3-7, 2022.